Peran Kepala Perpustakaan Dalam Penerapan Manajemen Perpustakaan SMPN 1 Rejang Lebong - Rhoni Rodin; Tasya Febrianti; Tsulist Agustin; Cut Afrina (Jurnal Gema Pustakawan, 2024)
This study aims to examine the implementation of library management at SMP Negeri 1 Rejang Lebong, covering planning, organizing, implementation, and evaluation. The goal of the library management at this school is to improve the quality of educational services by providing an effective and efficient library. The planning by the head librarian includes preparing short-term, medium-term, and long-term work plans, as well as developing the collection according to the curriculum needs and students' reading interests. Organizing involves assigning tasks to library staff based on expertise, managing human and physical resources, and arranging library facilities. The library's work program includes distributing textbooks to students at the beginning of the semester, acquiring new books every year, and conducting literacy activities to enhance students' reading interest. The implementation of library activities emphasizes regular and orderly book borrowing, as well as supporting educational programs. Evaluation is routinely carried out by the head librarian and the school to ensure the quality of library services. The results show that the library management at SMP Negeri 1 Rejang Lebong has been running well, although there are some challenges such as low student reading interest and book management issues. Efforts for improvement continue to be made to enhance the professionalism of library managers, service quality, and collaboration with other parties to systematically and purposefully achieve the library's goals.